Contrast agents in Nephrology - a literature review - Fernandes,Sara Cardoso (2019)
Contrast agents are widely used in ambulatory and hospitalized patients, as a complement to imaging studies, improving diagnostic accuracy. Patients with chronic kidney disease are at increased risk for adverse events related to contrast administration. In this review, we will summarize the current evidence on this topic.